Upaya guru Pendidikan Agama Islam dalam mengatasi kesulitan membaca al-Qur’an di SMK Muhammadiyah 2 Sragen - Aprilia Hana Saputri; Hafidz Hafidz (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
The purpose of this study are to describe the efforts of Islamic religious education teachers in overcoming students’ difficulties in reading the Qur.'an at SMK Muhammadiyah 2 Sragen and also to describe the supporting and inhibiting factors in the process of learning. This study uses a qualitative method with a type of field research using a phenomenological approach. Data collection techniques in this study are by observation, interviews and documentation. Data analysis used in this research is data reduction, data display (presentation of data), and drawing conclusions. The validity of the data in this study is through several sources, namely primary data sources and secondary data sources. The primary data sources in this study are curriculum vice principal, Islamic religious education teachers, and students of class XI TKR 2. Meanwhile, the secondary data sources is the documents. This study uses two triangulations, namely source triangulation and time triangulation. The results of this study states that the efforts implemented by Islamic religious education teachers in overcoming the students’ difficulties in reading the Qur'an are (1) Before the learning began, the habit of reading the Qur.'an is carried out (2) Grouping students according to their level in reading the Qur.'an (3) Applying reading-listening Qur.’an (4) Identifying and giving special attention. The supporting factors in efforts to overcome the students’ difficulties in reading the Qur.'an are from the role of the teacher and the school, the role of parents and the enthusiasm of students. While the inhibiting factor is the lack of time to study the Qur.'an, the lack of references to Al-Qur.'an textbooks and the lack of discipline of students.